2020
DOI: 10.1093/nsr/nwaa295
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation and manipulation of hot electrons at room temperature

Abstract: In modern electronics and optoelectronics, hot electron behaviors are highly concerned since they determine the performance limit of a device or system, like the associated thermal or power constraint of chips, the Shockley-Queisser limit for solar cell efficiency. Up-to-date, however, the manipulation of hot electrons is mostly based on conceptual interpretations rather than a direct observation. The problem arises from a fundamental fact that energy-differential electrons are mixed up in real-space, making i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…α H ( f = 1 Hz) of the as‐synthesized Bi 2 S 3 NWs was estimated to be ≈2 × 10 −5 , considering that α H is affected by surface defects, the low value of α H observed in the Bi 2 S 3 NWs can be attributed to the lack of surface defects. [ 49,50 ] Obviously, the value of α H is better than most reported 1D materials‐based devices. The reported performance of Bi 2 S 3 ‐based photodetectors synthesized via different approaches and some other nanostructure‐based photodetectors are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…α H ( f = 1 Hz) of the as‐synthesized Bi 2 S 3 NWs was estimated to be ≈2 × 10 −5 , considering that α H is affected by surface defects, the low value of α H observed in the Bi 2 S 3 NWs can be attributed to the lack of surface defects. [ 49,50 ] Obviously, the value of α H is better than most reported 1D materials‐based devices. The reported performance of Bi 2 S 3 ‐based photodetectors synthesized via different approaches and some other nanostructure‐based photodetectors are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 88%
“…Defects act as carrier traps play an important role in tailoring the optoelectronic properties of materials and adjusting 1/f noise, which is consistent with the previous report. [28,49,50] In this work, the sulfur-assisted vapor transport preparation method reduces S vacancies of the Bi 2 S 3 NWs, increasing optoelectronic performances while reducing 1/f noise. The combination of superior photoresponse properties and lower electrical noise in Bi 2 S 3 NWs provides excellent material and device platform for polarized imaging application.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that the light-induced photogating effect or hot-electron storing effect occurring at different surface energy levels of InAs NWs can alter the carrier relaxation process and endow them with sufficiently long lifetimes. , Also, charge trapping and detrapping at the interface between the native oxide layer of InAs NW and high- k dielectric Al 2 O 3 have been reported to endow the device with multiple memory states, enabling the emulation of the synaptic behavior . To understand the mechanism of the P­(VDF-TrFE)-coated InAs NW synaptic transistors, we also study the synaptic properties of the pristine device (as shown in Figure S7a,c) and compare them with those after the P­(VDF-TrFE) coating (as shown in Figure S7b,d).…”
Section: Resultsmentioning
confidence: 99%
“…NRs possess distinct and unique physical properties compared to two-dimensional or other dimensional counterparts have been demonstrated [1][2][3]. Due to the adjustable length, width, thickness of the synthesized NRs, resulting in the unique transport mechanisms of photons and electrons [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%